Pengaruh Penambahan NPK dalam Pendegradasian Limbah Cair Kelapa Sawit Menggunakan Biofiltrasi Anaerob dengan Reaktor Fixed-Bed - Yusuf, Amalia Sasmita Amalia; F, Panca Nugrahini (Universitas Negeri Semarang, 2019)
The processing of Liquid Palm Oil Waste using a fixed-bed reactor has disadvantages where the effluent of wastewater treatment are not balanced with nutrients or substrates available in both waste and activated sludge. For handling these problems, it is necessary to add nitrogen and phosphorus compounds in the form of NPK in activators. There are 3 variations of treatment for NPK, which are 2.5 grams and 5 grams without NPK. The final value of COD without NPK is 1.843 mg/l; 2.5 grams of NPK 623 mg/l; and 5 grams of NPK of 709 mg/l. The final value of TSS without NPK is 4.728 mg/L; 2.5 grams of NPK which is 4,098 mg/L; 5 grams of NPK 3,924 mg/l. The final value of VSS without NPK is 601 mg/l, 2.5 grams of NPK is 414 mg/l; and 5 grams of NPK which is 525 mg/l, From the results of the analysis it can be concluded that the best degradation is obtained by adding 2.5 grams of NPK